Synergetic improvement of technological characteristics of highway road surfaces by bitumen microdispersed emulsions - Anton O. Glazachev; Olga V. Ivanova; Stanislav Yu. Pavlov; Aleksandr S. Salov; Ranis M. Akhmetshin (Нанотехнологии в строительстве, 2024)
Introduction. The use of bitumen microdispersed emulsion as a resource-saving method for road surface construction is a popular trend in the development of innovative nanostructures. The technological use of petroleum bitumen as a binder for road materials requires a reduction in rheological viscosity. This can be achieved through synergistic developments that involve the use of various additives and modifiers. Methods and materials. The composition of bitumen microheterogeneous emulsions includes: bitumen-containing raw materials (up to 70–80% of mass); water with hardness up to 6 mg-eq/l (from 20 to 30%); emulsifiers (up to 3%) and other components. For large-tonnage production of water- bitumen emulsions, a colloid mill is the most technologically advanced equipment. Results. Water-bitumen emulsions are formed as a result of two competing processes: crushing (dispersion) and coalescence (merging) of microdroplets of the bitumen dispersed phase. The microheterogeneous bitumen phase is distributed in the aqueous dispersion medium in the form of microdroplets ranging in size from 1 to 10 μm (the main share is made up of bitumen microdroplets with a diameter of 2–4.5 μm). The synergetic durable microstructure of asphalt concrete road surfaces, which is formed by supplementing interaction in the boundary layers of the bitumen binder with the surface of the mineral component, is determined by the dominant interaction of complementary factors. Discussion. The synergetic approach to extending the service life of asphalt concrete road surfaces by using bitumen microdispersed emulsions holds promise for interpreting their evolution. The road construction industry of the Russian Federation at the beginning of the 21st century is characterized by a large-scale revision of regulatory documents, regulating the requirements for the construction and operation of highways. Conclusion. The optimal solution to the current problems of intensive construction and reconstruction of Russian highways is the improvement of technological characteristics of road surfaces by adding bitumen microdispersed emulsions to the composition. In complementary strengthening of weak soils of the road surface of high-speed highways, the use of water-bitumen microdispersed emulsions is also recommended.